Censorship detected in MM (Myanmar) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Myanmar. Data sourced from OONI.
Censorship Incident ID: MM-2026-1991. Severity: critical. Confidence: 90%